Reflection of hate speech on ethnic satellite channels on the public - Ahmed kareem Ahmed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Hate speech can refer to any expressions that encourage incitement to cause harm in all forms of discrimination or aggression or the use of violence according to the target entity or person Through this research, the researcher seeks to reveal the extent of the reflection of hate speech in the Iraqi media on Iraqi society, and this research is classified among the descriptive studies, where the researcher used the survey method to answer the questions of the research problem represented by the main question: ethnic on audience The research community was represented by the Iraqi public, and the researcher resorted to choosing the available sample within the framework of non-probability samples, and the research sample was limited to (250) individual members of the Iraqi communit. DOI /10.54633/2333-021-042-016